Hedonic price analysis of urban housing：An empirical research on Hangzhou, China - 温海珍 贾生华 郭晓宇 (Journal of Zhejiang University. A. Science, 2005)
The hedonic price model is widely applied to study the urban housing market because of the heterogeneity of housing products. Literature indicated that the hedonic price theory mainly includes two parts： Lancaster＇s partiality theory and Rosen＇s characteristic market equilibrium analysis. This paper chose 18 characteristics as independent variables and set up a linear hedonic price model for Hangzhou City. The model was tested with 2473 housing samples and field survey data of 290 housing communities. This research found that 14 out of 18 characteristics had significant influence on housing price. They were classified into 5 groups according to their impact degree.